The amber industry: development challenges and combating amber trafficking in the Baltic region = Проблемы развития янтарной отрасли и противодействие незаконному обороту янтаря в Балтийском регионе - Volchetskaya, Т. S (2017)
This article considers the current state and prospective development of the amber industry in the Baltic Sea region. The authors identify the main obstacles to the industry's development in Russia - poor pricing mechanisms for raw amber, an imbalance between supply and demand, a slow pace of technological modernisation, and a delayed introduction of new technologies and processing techniques. The authors identify gaps in the regulatory framework and highlight problems of legal regulation and law enforcement as regards the amber industry. Combating illegal amber extraction and trafficking is a pressing problem in the Kaliningrad region (Russia) and other Baltic region states. The article explores theoretical aspects of the legislative policy on combating illegal amber extraction and trafficking. The authors focus on the relevant law enforcement practices and hold that administrative sanctions for unauthorised amber extraction and trade are not fully effective in Russia. The authors